Attitudes of Students at The Faculty of Educational Sciences at The University of Jordan towards Inclusion Students with Autism Spectrum Disorder into Public Schools - El-Shara, Ibrahim A.; Al-Jabri, Mohammad A.; Bensaci, Okil M. (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed at exploring the attitudes of Faculty of Educational Sciences’ students at the University of Jordan towards inclusion students with autism spectrum disorder into regular schools, and to find out whether there are differences depending on the variables of the academic year and the cumulative average. Methods: The study followed a descriptive survey approach by developing an instrument of (31) items distributed over three sub-domains related to attitudes toward: cognitive and academic inclusion, psychological and emotional inclusion, and behavioral and social inclusion, which had acceptable validity and reliability. Results: The results indicated that students’ attitudes toward the inclusion of autism spectrum disorder were moderate on total and on sub-dimensions. Whereas students’ attitudes towards the behavioral and social ranked first, and the emotional and psychological ranked least. Also, the results showed that there were no significant differences due to the variables of academic year and cumulative average. Conclusions: The study concluded that attitudes toward the inclusion of autism spectrum disorder are generally positive, and that students moderately support the right to include students of this category into public schools. It highlighted the positive impact that this inclusion will have on these students in cognitive, academic, social, emotional, and psychological domains. The study recommended the necessity of supporting and maintaining these attitudes as these students will eventually work in the future as teachers for students with autism spectrum disorder when they join the schools. This supports Jordan's movement towards implementing the provisions of the ten-year plan related to spreading a culture of inclusion for students with disabilities.